Planned change theories for nursing review, analysis, and implications - Tiffany, Constance Rimmer; Lutjens, Louette R. Johnson; Sage eBooks (Thousand Oaks, [Calif.] ; London : SAGE, 1998)
This book is designed to enable nurses to understand the process of planned change. The authors present overviews of 3 widely accepted change theories and show the implications of the theories for nursing practice.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Nursing -- Planning; Organizational change; Social change; Nursing models; Electronic books